Analysis of mortality factors in ICU patients with sepsis and septic shock: a retrospective study - Mohammed Mostafa; Lamiaa Hamed; Sherif Mokhtar; Moamen Arafa (Egyptian Journal of Critical Care Medicine)
Abstract Background Sepsis and septic shock are critical conditions that pose significant challenges in intensive care units (ICUs), characterized by a dysregulated host response to infection, leading to organ dysfunction and high mortality rates. The increasing incidence of sepsis necessitates a thorough understanding of the factors influencing patient outcomes. Aim This study aims to analyze the mortality rates among ICU patients diagnosed with sepsis and septic shock, focusing on the role of organ dysfunction, age, and the Acute Physiology and Chronic Health Evaluation II (APACHE II) score. Methods A retrospective analysis was conducted on 200 patients diagnosed with sepsis and septic shock admitted to the ICU over 2 years. Data were collected on patient demographics, including age, gender, comorbidities, and APACHE II scores calculated upon admission. Organ dysfunction was assessed based on clinical criteria, and mortality rates were tracked throughout the ICU stay. Statistical analyses were performed using SPSS software, with significance at p < 0.05. Results The cohort consisted of 200 patients, with a mean age of 65 years (SD ± 12.3). The overall mortality rate was found to be 54.5%, with significant differences observed between survivors and non-survivors. The mean APACHE II score for the entire cohort was 20.35 (SD ± 6.5), with non-survivors exhibiting a mean score of 23.77 (SD ± 5.8) compared to 15.87 (SD ± 4.2) for survivors (p < 0.001). Cardiovascular dysfunction was prevalent in 75% of septic patients, contributing to a mortality rate of 54.5%. These findings underscore the importance of early identification and management of organ dysfunction to improve patient outcomes. Conclusion This study highlights the critical role of APACHE II scores and cardiovascular dysfunction in predicting mortality among ICU patients with sepsis and septic shock. The high mortality rates associated with these factors emphasize the need for proactive management strategies and tailored interventions to enhance patient survival and improve overall outcomes in this vulnerable population.